Pendampingan Strategi Pembelajaran Kelas Gabungan Melalui Penerapan Reward System untuk Meningkatkan Motivasi Belajar Siswa pada Program “Speak Up Cendekia” - Ni Wayan Mia Noviyanti; I Komang Nada Kusuma; I Wayan Numertayasa (FKIP, Universitas Palangka Raya, 2026)
This community service program aims to increase student learning motivation through the implementation of a reward system in a combined class of fifth and sixth grade students at SD N 5 Rendang. This activity was carried out through collaboration between teachers and students of the Community Service Program (KKN) in Rendang Village. The approach used was descriptive qualitative through direct observation and reflection on student learning behavior during the learning process. Before the program was implemented, students showed a passive attitude and did not dare to ask questions and express opinions. After the implementation of the reward system, there was a significant increase, from initially only about 3 active students to about 12 people, out of a total of 17 students in two grade levels. After the program implementation, students became more enthusiastic, confident, and willing to participate in the learning process, and a healthy competitive atmosphere emerged between the two grade levels. Teachers, especially homeroom teachers, found that learning activities became more dynamic and enjoyable, while students themselves gained valuable experience in classroom management and improved communication skills with students. The results of this activity indicate that collaborative learning combined with a reward system can effectively increase learning motivation and encourage active student participation in the context of a combined class. Overall, this program has had a positive impact on teachers, students and KKN students in creating a more interactive and enjoyable learning experience.